Demographics and Personality Factors Associated with Burnout among Nurses in a Singapore Tertiary Hospital. (12th July 2016) - Ang, Shin Yuh; Dhaliwal, Satvinder S.; Ayre, Tracy Carol; Uthaman, Thendral; Fong, Kuan Yok; Tien, Choo Eng; Zhou, Huaqiong; Della, Phillip
Abstract : Background . The aim of the study was to evaluate the prevalence and extent of burnout among nurses in Singapore and investigate the influence of demographic factors and personal characteristics on the burnout syndrome. Methods . A cross-sectional survey design was adopted. All registered nurses working in Singapore General Hospital were approached to participate. A questionnaire eliciting data on demographics, burnout (measured using the Maslach Burnout Inventory, MBI), and personality profile (measured using the NEO Five-Factor Inventory, NEO-FFI) was used. Results . 1830 nurses out of 3588 responded (response rate: 51%). Results from 1826 respondents were available for analysis. The MBI identified 39% to have high emotional exhaustion (EE, cut-off score of >27), 40% having high depersonalization (DP, cut-off score of >10), and 59% having low personal accomplishment (PA, cut-off score of <33). In multivariable analysis, age, job grade, and neuroticism were significantly associated with each of the 3 components of the MBI. Staff nurses less than 30 years with high to very high neuroticism were more likely to experience high EE, high DP, and low PA. Conclusion . Younger nurses in Singapore are at increased risk of burnout. Personality traits also played a significant role in the experience of burnout.